Diagnostic and Management Approach of Obesity with Multiple Complications in a Child: A Case Report - Siti Azura Putri Dilla Sari; Cut Nurul Hafifah (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Adults with obesity may already experience obesity during childhood or adolescence, highlighting the critical importance of early intervention. This is particularly concerning given that childhood obesity, a growing component of Indonesia's "triple burden of malnutrition," significantly increases the risk of developing severe non-communicable diseases and reducing life expectancy. Case: A 10-year-old male patient presented with a chief complaint of shortness of breath for the past two weeks, worsened when lying down and improved when sitting up. The patient also snored, often woke up due to difficulty breathing. The patient had experienced rapid weight gain since the age of 2 years. He ate in large portions, frequently snacked, and consumed sugary drinks daily. He had no regular physical activity and was mostly sedentary. He showed signs of obesity (BMI 35.8 kg/m²), short stature, and physical abnormalities including a rounded face, double chin, acanthosis nigricans, and bowed legs. Discussion: Diagnosing obesity requires comprehensive history and physical examination to distinguish between primary and secondary causes.  Our patient's early-onset obesity and hyperphagia prompted leptin level evaluation, although the result was within normal limit, leptin resistance or receptor imbalance was suspected. In this case, familial lifestyle factors appear to play a role, highlighting the importance of a family-centered approach. Management of obesity includes dietary modification, physical activity, sleep and behavioral regulation, and pharmacologic therapy when indicated. Conclusion: An accurate diagnostic approach is crucial to guide optimal management strategies in complicated cases of obesity.